Monitoring stress responses in cyanobacterial scytonemin--screening and characterization - Mushir, Saman (Environmental technology, 2012)
Scytonemin is believed to protect a variety of organisms against the negative effects of ultraviolet radiation. Cyanobacteria have evolved different strategies to minimize the potential damage caused by solar ultraviolet radiation. This includes the synthesis of the UV-absorbing compound scytonemin, which acts as a sunscreen. During the present study scytonemin was found in 9 out of 19 studied cyanobacterial strains. Aulosira fertilissima showed the maximum amount of scytonemin. The effect of environmental factors, including temperature, light intensity, UV-light and salt was studied on scytonemin synthesis of A. fertilissima. A remarkable change in scytonemin synthesis was observed under salt stress and UV-light stress. Scytonemin increased under all stress conditions but it increased maximally under yellow-light stress